2016
DOI: 10.1016/j.ajhg.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Truncating Mutations in the Adhesion G Protein-Coupled Receptor G2 Gene ADGRG2 Cause an X-Linked Congenital Bilateral Absence of Vas Deferens

Abstract: In 80% of infertile men with obstructive azoospermia caused by a congenital bilateral absence of the vas deferens (CBAVD), mutations are identified in the cystic fibrosis transmembrane conductance regulator gene (CFTR). For the remaining 20%, the origin of the CBAVD is unknown. A large cohort of azoospermic men with CBAVD was retrospectively reassessed with more stringent selection criteria based on consistent clinical data, complete description of semen and reproductive excurrent ducts, extensive CFTR testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(92 citation statements)
references
References 34 publications
4
83
1
4
Order By: Relevance
“…We performed exome sequencing on the three members of family 1 (father, mother, and affected boy) and on all four members of family 2 (father, mother, affected boy, and unaffected sister). The summary of exome sequencing data for the probands and their parents is reported in (Imsland et al, 2012), ADGRD2was an adhesion G-protein-coupled recently involved in absence of the vas deferens (Patat et al, 2016), BMP15 is involved in ovarian function (de Castro, Cruz, & Leal 2016), and HEPH is involved in iron metabolism (Jiang et al, 2015). As patient 2 had myoclonic seizures, we searched for any second variant in the 33 known genes involved in epileptic encephalopathy (Epi4K Consortium et al, 2013) but we did not identified de novo or inherited variant in this list of genes suggesting either the occurrence of another variant in an unknown epilepsy genes or the non-specific epileptic status of patient 2.…”
Section: Exome Analysis Revealed Two Different Splice Variants In Thementioning
confidence: 99%
“…We performed exome sequencing on the three members of family 1 (father, mother, and affected boy) and on all four members of family 2 (father, mother, affected boy, and unaffected sister). The summary of exome sequencing data for the probands and their parents is reported in (Imsland et al, 2012), ADGRD2was an adhesion G-protein-coupled recently involved in absence of the vas deferens (Patat et al, 2016), BMP15 is involved in ovarian function (de Castro, Cruz, & Leal 2016), and HEPH is involved in iron metabolism (Jiang et al, 2015). As patient 2 had myoclonic seizures, we searched for any second variant in the 33 known genes involved in epileptic encephalopathy (Epi4K Consortium et al, 2013) but we did not identified de novo or inherited variant in this list of genes suggesting either the occurrence of another variant in an unknown epilepsy genes or the non-specific epileptic status of patient 2.…”
Section: Exome Analysis Revealed Two Different Splice Variants In Thementioning
confidence: 99%
“…Congenital bilateral absence of vas deferens (CBAVD, MIM: 277180) is an important cause of male infertility and obstructive azoospermia, accounting for 1–2% of the infertile population (Yu et al ., ). CBAVD involves a complete or partial defect of the Wolffian duct derivatives and may occur either as an isolated reproductive disorder or as an atypical symptom of (CF, MIM: 219700)(Patat et al ., ). Appropriately, isolated CBAVD is suggested to share a common genetic mechanism with CF, because nearly all men with CF also exhibit CBAVD and are infertile owing to obstructive azoospermia (Chillon et al ., ; Wilschanski et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…These obstructions can be caused by a congenital unilateral or bilateral absence of the vas deferens. The most common genetic cause of obstructive azoospermia (OA) are biallelic variants in the CFTR gene (Anguiano et al 1992; Culard et al 1994; Dumur et al 1990; Oates and Amos 1994; Patrizio et al 1993) and variants in the recently identified X-linked gene ADGRG2 (Patat et al 2016).…”
Section: Resultsmentioning
confidence: 99%